2014
DOI: 10.1007/s10863-014-9564-x
|View full text |Cite
|
Sign up to set email alerts
|

An update on complex I assembly: the assembly of players

Abstract: Defects in Complex I assembly is one of the emerging underlying causes of severe mitochondrial disorders. The assembly of Complex I has been difficult to understand due to its large size, dual genetic control and the number of proteins involved. Mutations in Complex I subunits as well as assembly factors have been reported to hinder its assembly and give rise to a range of mitochondria disorders. In this review, we summarize the recent progress made in understanding the Complex I assembly pathway. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…RNAi-mediated knockdown of dNDUFS2, dNDUFS3, dNDUFS5, dNDUFS7, and dNDUFS8 led to a reduction in the amount of the ~815 kDa assembly intermediate (relative to wild type), as they impaired some of the initial steps of CI biogenesis (Figures 4B and C). In addition, the amount of the ~315 kDa assembly intermediate was drastically reduced when the expression of dNDUFS2, dNDUFS3, or dNDUFS7 was impaired (Figure 4B); in line with our proteomic results in Figure 3D and current mammalian CI assembly models that show that the first step in CI biogenesis involves the formation of an assembly intermediate consisting of NDUFS2 and NDUFS3 (Figure 3B) [reviewed in (Vartak et al, 2014)]. Notably, we found that RNAi-mediated knockdown of dNDUFA5 depleted the ~315 kDa assembly intermediate (Figure 4C).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…RNAi-mediated knockdown of dNDUFS2, dNDUFS3, dNDUFS5, dNDUFS7, and dNDUFS8 led to a reduction in the amount of the ~815 kDa assembly intermediate (relative to wild type), as they impaired some of the initial steps of CI biogenesis (Figures 4B and C). In addition, the amount of the ~315 kDa assembly intermediate was drastically reduced when the expression of dNDUFS2, dNDUFS3, or dNDUFS7 was impaired (Figure 4B); in line with our proteomic results in Figure 3D and current mammalian CI assembly models that show that the first step in CI biogenesis involves the formation of an assembly intermediate consisting of NDUFS2 and NDUFS3 (Figure 3B) [reviewed in (Vartak et al, 2014)]. Notably, we found that RNAi-mediated knockdown of dNDUFA5 depleted the ~315 kDa assembly intermediate (Figure 4C).…”
Section: Resultssupporting
confidence: 84%
“…At this point, the ~815 kDa assembly intermediate is generally considered to be composed of the complete Q and P modules. Finally, an independently-formed assembly intermediate consisting of NDUFS1, NDUFV1, NDUFV2, NDUFV3, NDUFS4, NDUFS6 and NDUFA12 which together form the N module, is added as a “cap” to the ~815 kDa assembly intermediate to produce the ~950 kDa holoenzyme [Figure 3B; the ~315-, ~370-, ~550-, and ~815 kDa assembly intermediates were previously estimated as ~400-, ~460-, ~650- and ~830 kDa subcomplexes respectively (Andrews et al, 2013; Vartak et al, 2014)].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of complex I concerns the nuclear-encoded accessory subunits NDUFA7, NDUFA10, NDUFC2, NDUFS4, ESSS and GRIM-19, which have been implemented with the assembly of the 45-subunit complex (De Rasmo et al, 2010;Palmisano, Sardanelli, Signorile, Papa, & Larsen, 2007;Vartak, Semwal, & Bai, 2014). Cytochrome c oxidase is phosphorylated at no less than 18 positions facing both the matrix and intermembrane space of the mitochondrion (Helling, Hüttemann, Kadenbach, et al, 2012;Helling, Hüttemann, Ramzan, et al, 2012).…”
Section: Protein Phosphorylationmentioning
confidence: 99%
“…Assembly processes of the major RMPs, including quinol: cytochrome c oxidoreductases (Hasan, Proctor, Yamashita, Dokholyan, & Cramer, 2014;Hasan, Yamashita, & Cramer, 2013;Smith, Fox, & Winge, 2012), terminal oxidases (Bühler et al, 2010;Ekici, Pawlik, Lohmeyer, Koch, & Daldal, 2012;Gurumoorthy & Ludwig, 2015), nitrite-/nitric oxide-/nitrous oxide reductases (Adamczack et al, 2014;Barth, Isabella, & Clark, 2009;Hatzixanthis, Richardson, & Sargent, 2005;Nicke et al, 2013;Spiro, 2012), hydrogenases (Peters et al, 2015), formate dehydrogenases (Hartmann, Schwanhold, & Leimkühler, 2015) and other molybdopterin-containing RMPs (Arnoux et al, 2015;Magalon & Mendel, 2015), have been studied in more or less detail. Notoriously, the assembly of complex I with its about 45 subunits in unicellular and higher eukaryotes is puzzling (Mimaki et al, 2012;Vartak et al, 2014;Vogel, Smeitink, & Nijtmans, 2007). Assembly should be much simpler for prokaryotic NDHs that harbour a mere 13 subunits, but virtually nothing is known about it.…”
Section: Assembly Of Bacterial Respiratory Complexesmentioning
confidence: 99%
“…The electron transfer between binding sites provides a sufficient amount of energy for structural alterations, which facilitate the outward proton flux. In the next stage the trans-membrane electrochemical potential difference, generated in the oxidation process, is used for ATP production [48][49][50][51][52]. Equation (7) summarizes the ATP synthesis process.…”
Section: The Functioning Of a Molecular Machinementioning
confidence: 99%